2018
DOI: 10.1016/j.ahj.2018.03.017
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between baseline and follow-up left ventricular ejection fraction with adverse events among primary prevention ICD patients

Abstract: Among primary prevention ICD recipients, both baseline and follow-up LVEF were independently associated with long-term risk for appropriate ICD therapy, but they were not associated with time to the composite of LVAD, transplant, or death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…All-cause mortality of 30.5% in the Townsville district was 1.2 to 2 times higher than mortality reported in other cohort studies in Australia, New Zealand, North America and Europe (15,(17)(18)(19)(20). Although we found no significant difference in mortality between the ICM and NICM patients, the total mortality in ICM patients was 1.4 to 2.4 times those in the MADIT, MADIT II, and MUST trials (21,22), and 1.3 to 2.8 times higher in the NICM patients compared to the CAT, AMIOVIRT, DEFINITE, and recent DANISH trials (23-26).…”
Section: Mortality Was Higher In Regional North Queenslandcontrasting
confidence: 56%
See 1 more Smart Citation
“…All-cause mortality of 30.5% in the Townsville district was 1.2 to 2 times higher than mortality reported in other cohort studies in Australia, New Zealand, North America and Europe (15,(17)(18)(19)(20). Although we found no significant difference in mortality between the ICM and NICM patients, the total mortality in ICM patients was 1.4 to 2.4 times those in the MADIT, MADIT II, and MUST trials (21,22), and 1.3 to 2.8 times higher in the NICM patients compared to the CAT, AMIOVIRT, DEFINITE, and recent DANISH trials (23-26).…”
Section: Mortality Was Higher In Regional North Queenslandcontrasting
confidence: 56%
“…However, in our study 67 patients did not experience ventricular arrhythmias over the duration of 4.8 years, which needs to be taken into consideration when determining a therapy's success rate. An appropriate therapy rate of 18% sits at the lower end of the published range of 11.6 to 24% over 2.1-3.64 years follow-up (11,15,19,20,(28)(29)(30)(31). In a large randomized control trial of 2,521 patients Bardy showed a 21% appropriate shock rate in the ICD arm (32,33).…”
Section: Only 19% Of Patients Received Appropriate Icd Therapymentioning
confidence: 99%
“…77 • An improvement in LVEF during long-term follow-up is a frequent finding after implant of an ICD, even above 35%, but it is not associated with lack of appropriate device interventions for malignant ventricular tachyarrhythmias thus suggesting that the risk of ventricular tachyarrhythmias and SCD is modulated by pharmacological treatments, but a residual risk persists, along with time, that in appropriate patients may surely benefit from the rescue role of a back-up ICD. [78][79][80][81] • In patients implanted with an ICD or a CRT-D appropriate ICD shocks (especially when clustered into electrical storms) are associated with a significant increase in the subsequent risk of all-cause death 82,83 and therefore the occurrence of shocks, even if appropriate, should be considered a warning sign of a worsening prognosis. 84 Implementation of sacubitril/valsartan is in these cases absolutely appropriate in order to implement the favourable effects of this agent on ventricular tachyarrhythmias.…”
Section: Sacubitril/valsartan: Impact On Cardiovascular Mortality and On Sudden Cardiac Deathmentioning
confidence: 99%
“…Decreased LVEF imposes an elevated risk for clinical events that can coincidently benefit from optimal medical treatments, complicating the interpretation of LVEF for outcome prediction in secondary prevention. 27 However, CRC is valuable for monitoring medical therapy for secondary prevention of HF. Therefore, these findings would also extend the clinical implications of CRC as a prognostic indicator to patients with HF undergoing medical treatment.…”
Section: Discussionmentioning
confidence: 99%